2017
DOI: 10.1111/1755-5922.12265
|View full text |Cite
|
Sign up to set email alerts
|

RVX 208: A novel BET protein inhibitor, role as an inducer of apo A‐I/HDL and beyond

Abstract: Low-density cholesterol (LDL) has been the prime target of currently available lipid-lowering therapies although current research is expanding the focus beyond LDL lowering and has included high-density cholesterol (HDL) also as the target. Bromo and extra-terminal (BET) proteins are implicated in the regulation of transcription of several regulatory genes and regulation of proinflammatory pathways. As atherosclerosis is an inflammatory pathway and studies showed that BET inhibition has a role in inhibiting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 75 publications
0
27
0
Order By: Relevance
“…In CRISPR-edited stem cell-derived human ECs, the deletion of rs9349379 increased the gene expression of endothelin 1 (EDN1), which is located 600 kb upstream of PHACTR1. Interestingly, 4C-seq revealed a very low contact probability between rs9349379 and the EDN1 promoter, but a relatively high contact probability between rs9349379 and the EDN1 downstream SEs marked with high levels of H3K27ac, suggesting a potential role of rs9349379 in SE function (Gupta et al, 2017). In addition, cardiovascular disease-related SNPs are highly enriched in vascular endothelial growth factor (VEGF)-regulated compartments.…”
Section: Discussionmentioning
confidence: 99%
“…In CRISPR-edited stem cell-derived human ECs, the deletion of rs9349379 increased the gene expression of endothelin 1 (EDN1), which is located 600 kb upstream of PHACTR1. Interestingly, 4C-seq revealed a very low contact probability between rs9349379 and the EDN1 promoter, but a relatively high contact probability between rs9349379 and the EDN1 downstream SEs marked with high levels of H3K27ac, suggesting a potential role of rs9349379 in SE function (Gupta et al, 2017). In addition, cardiovascular disease-related SNPs are highly enriched in vascular endothelial growth factor (VEGF)-regulated compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, phase II trials showed that RVX-208 reduces MACE in treated patients, over and above that of apoA-I/HDL increasing action. This MACE reducing actions of RVX-208 is largely due to its novel anti-inflammatory actions [193,194]. Currently, a phase III trial, BETonMACE, is ongoing to look for the effects of RVX-208 in CVD patients.…”
Section: Rvx-208 (Apabetalone)mentioning
confidence: 99%
“…These findings offered a possible mechanism of inhibitor action. With these encouraging effects, BET inhibitors offer new therapeutic possibilities, mainly for blood cancers and inflammation (Belkina & Denis, 2012;Ceribelli et al, 2014;Berthon et al, 2016;Ghosh et al, 2017). With these encouraging effects, BET inhibitors offer new therapeutic possibilities, mainly for blood cancers and inflammation (Belkina & Denis, 2012;Ceribelli et al, 2014;Berthon et al, 2016;Ghosh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These drugs also inhibit inflammation and ameliorate related diseases, including LPSinduced sepsis, EAE-based neuroinflammation, diabetes, and cardiovascular diseases (Nicodeme et al, 2010;Bandukwala et al, 2012;Anand et al, 2013;Belkina et al, 2013;Mele et al, 2013;Brown Jonathan et al, 2014;Fu et al, 2014;Duan et al, 2017). With these encouraging effects, BET inhibitors offer new therapeutic possibilities, mainly for blood cancers and inflammation (Belkina & Denis, 2012;Ceribelli et al, 2014;Berthon et al, 2016;Ghosh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%